ASSOCIATION BETWEEN GLP-1 ANALOGUES AND PANCREATITIS: AN INTEGRATIVE REVIEW OF CURRENT EVIDENCE - Pereira, Alexandre Alves Neves; Soares, Júlia Mateus; Maia, Rafaela Cristina Bandeira; Bezerra, Júlio César Gomes; Freitas, Heitor Bernardo; Gonçalves, Nathalia Santos; Dadam Junior, Charles Albani; Döbele, Leonardo dos Santos; dos Santos Neto, Roberto de Moraes Ferreira; Oliveira, Luiz Henrique Menezes; Siqueira, Yuri Papacosta; Marinho, Marcella de Fátima Lomeu; et al. (Seven Editora, 2026)
Glucagon-like peptide-1 (GLP-1) receptor agonists have been widely used in the treatment of Type 2 Diabetes Mellitus and obesity due to their effectiveness in glycemic control and weight reduction. However, concerns regarding their pancreatic safety, particularly the risk of acute pancreatitis, have been raised in the scientific literature. This study aimed to analyze the association between the use of GLP-1 analogues and the occurrence of pancreatitis through an integrative literature review. The search was conducted in PubMed/MEDLINE, SciELO, and LILACS, including studies published between 2016 and 2026. Original articles, observational studies, systematic reviews, meta-analyses, and clinical guidelines available in full text were included. The results demonstrated that GLP-1 analogues have a well-established efficacy profile; however, findings regarding pancreatitis risk are heterogeneous. Observational studies suggest a possible association, whereas systematic reviews do not demonstrate a statistically significant increase in risk, indicating a low absolute risk and no definitive causal relationship. It is concluded that, although a direct causal association cannot be established, caution is recommended when prescribing these drugs, especially in patients with risk factors, and further studies are needed to better clarify this potential relationship.